2021
DOI: 10.1029/2020jg006182
|View full text |Cite
|
Sign up to set email alerts
|

Low Biodegradability of Dissolved Organic Matter From Southeast Asian Peat‐Draining Rivers

Abstract: Southeast Asia's extensive tropical peatlands account for a significant proportion of the global riverine dissolved organic carbon (DOC) flux to the ocean. Peat‐derived DOC is rich in polyphenolic compounds, the microbial degradation of which is thought to rely on extracellular phenol oxidases. Despite substantial interest in the biogeochemical fate of terrigenous DOC (tDOC), few studies have quantified phenol oxidase activity in aquatic environments, and microbial remineralization rates of tDOC have never bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 95 publications
2
17
1
Order By: Relevance
“…Although the leucine and glucose added as labile carbon to one treatment was rapidly consumed, no additional remineralization of DOC was induced in this treatment. Our results, consistent with the low biodegradability of tDOC from the Maludam River (Nichols & Martin, 2021), suggest that direct microbial remineralization is not a main driver of tDOC remineralization. Whether the observed biodegradation represents loss of tDOC at all or only of autochthonous DOC is unclear.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Although the leucine and glucose added as labile carbon to one treatment was rapidly consumed, no additional remineralization of DOC was induced in this treatment. Our results, consistent with the low biodegradability of tDOC from the Maludam River (Nichols & Martin, 2021), suggest that direct microbial remineralization is not a main driver of tDOC remineralization. Whether the observed biodegradation represents loss of tDOC at all or only of autochthonous DOC is unclear.…”
Section: Resultssupporting
confidence: 89%
“…For the δ 13 C of the DIC produced from remineralization, microbial respiration causes little carbon isotopic fractionation, while results from our experiments (Section 3.6) and previous studies (Opsahl & Zepp, 2001; Osburn et al., 2001; Spencer et al., 2009) indicated that photodegradation (and combined photo‐bio‐degradation) of tDOC can cause fractionation in δ 13 C of −1.4 to −5.8‰ between the produced DIC and the initial DOC (Table ). Because of the low bio‐degradability (Nichols & Martin, 2021) but high photo‐degradability of Southeast Asian peatland tDOC (Section 3.6), we infer that a major part of the remineralization of tDOC in this region might be via photodegradation, and therefore entails a carbon isotopic fractionation. We adopted a fractionation of −3‰, and thus used −32‰ as the δ 13 C of the DIC produced from tDOC remineralization.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…The environmental implications of rising tDOC in coastal waters depend on its biogeochemical fate. Peat-derived tDOC in Southeast Asia often mixes conservatively across estuaries ( 16 , 38 , 54 ) and appears to be relatively refractory to direct microbial remineralization, but is labile to photooxidation ( 12 , 55 ). Research off Sumatra suggests that the majority of peatland tDOC that reaches coastal waters is remineralized within the Sunda Shelf Sea over time scales of 1 to 2 years, resulting first in ocean acidification before gradually degassing to the atmosphere ( 12 , 56 ).…”
Section: Resultsmentioning
confidence: 99%